2018
DOI: 10.1111/1911-3846.12368
|View full text |Cite
|
Sign up to set email alerts
|

Auditing Complex Estimates: How Do Construal Level and Evidence Formatting Impact Auditors' Consideration of Inconsistent Evidence?

Abstract: The Public Company Accounting Oversight Board is concerned about auditors' tendency to ignore relevant information that is inconsistent with management's assumptions underlying complex estimates. We find that priming auditors to consider how management arrived at a particular assumption helps curb aggressive reporting by encouraging auditors to engage in low‐level, concrete thinking regarding the direct evidence underlying the assumption. Low‐level, concrete thinking enhances auditors' sensitivity to relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 38 publications
4
41
0
Order By: Relevance
“…We requested that the surveys be distributed to audit partners with experience auditing FVMs. 7 The firms' contacts distributed surveys to potential 4 We acknowledge a growing number of experimental studies that investigate how various environmental and task factors affect auditors' judgments and decisions when auditing FVMs (e.g., Backof, Thayer, and Carpenter 2015;Earley, Hoffman, and Joe 2015;Griffin 2014;Griffith, Hammersley, Kadous, and Young 2015b;Joe, Vandervelde, and Wu 2017;Joe, Wu, and Zimmerman 2016;Maksymov, Nelson, and Kinney 2015;Pyzoha, Taylor, and Wu 2016). 5 Results presented in the current study are part of a larger survey, including results reported in Glover et al (2016).…”
Section: Data Collectionmentioning
confidence: 99%
“…We requested that the surveys be distributed to audit partners with experience auditing FVMs. 7 The firms' contacts distributed surveys to potential 4 We acknowledge a growing number of experimental studies that investigate how various environmental and task factors affect auditors' judgments and decisions when auditing FVMs (e.g., Backof, Thayer, and Carpenter 2015;Earley, Hoffman, and Joe 2015;Griffin 2014;Griffith, Hammersley, Kadous, and Young 2015b;Joe, Vandervelde, and Wu 2017;Joe, Wu, and Zimmerman 2016;Maksymov, Nelson, and Kinney 2015;Pyzoha, Taylor, and Wu 2016). 5 Results presented in the current study are part of a larger survey, including results reported in Glover et al (2016).…”
Section: Data Collectionmentioning
confidence: 99%
“…Downloaded from http://meridian.allenpress.com/doi/pdf/10.2308/tar-2016-0223 by guest on 01 August 2020 pursuit in favor of management's position will be less likely to recommend impairment. Consistent with the approach taken in prior research, the presence of contradictory evidence indicates an increased likelihood of impairment and greater potential for management bias/aggressiveness in the estimate (e.g., Wilks 2002;Griffith et al 2015b;Koch and Salterio 2017;Backof, Carpenter, and Thayer 2018). Consequently, a higher likelihood of recommending impairment (i.e., less likely to accept management's position) represents a higher-quality audit judgment.…”
Section: Dependent Variablementioning
confidence: 52%
“…12 This case is adapted from the case used in Backof, Carpenter, and Thayer (2018). Two practicing audit partners and two practicing audit managers from different Big 4 accounting firms reviewed the current case materials for relevance and representativeness of actual audit workpapers.…”
Section: Procedures and Designmentioning
confidence: 99%